2014
DOI: 10.3892/ijo.2014.2749
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Msi1 suppresses the growth of human colon cancer by targeting p21cip1

Abstract: Abstract. Musashi1 (Msi1), a member of the RNA-binding protein (RBP) family, is highly expressed in neural progenitor or stem cells for the maintenance of stemness as well as in various cancers. Emerging studies have demonstrated that it regulates cell processes by translational activation or suppresses specifically bound mRNA. In the present study, we initially reported remarkably increased expression of Msi1 in colon cancer tissues compared with adjacent nontumor tissues. Knockdown of Msi1 significantly supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Our results have relevance to the role of MSI-2 in human colon tumorigenesis because several studies have previously investigated MSI-1 and reported that MSI-1 is expressed in low levels in normal colonic tissue and high levels in CRCs [ 18 , 19 ]. While less is known about MSI-2, a study by Wang, et al reported that MSI-2 is overexpressed in human CRCs.…”
Section: Resultsmentioning
confidence: 54%
“…Our results have relevance to the role of MSI-2 in human colon tumorigenesis because several studies have previously investigated MSI-1 and reported that MSI-1 is expressed in low levels in normal colonic tissue and high levels in CRCs [ 18 , 19 ]. While less is known about MSI-2, a study by Wang, et al reported that MSI-2 is overexpressed in human CRCs.…”
Section: Resultsmentioning
confidence: 54%
“…We also found that the amino acid residues that are involved in RNA-binding are conserved in Msi1 and its paralog, Msi2. Elevated expression of Msi1 and Msi2 has been identified in a large variety of tumors arising in the bladder, brain, breast, colon, lung, ovary, pancreas, and others [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Additionally, increased expression of Msi1 and Msi2 has been found in leukemias such as acute myelogenous leukemia and acute lymphoblastic leukemia [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased expression of Msi1 and Msi2 has been found in leukemias such as acute myelogenous leukemia and acute lymphoblastic leukemia [ 13 , 14 , 15 , 16 , 17 ]. Msi1 and Msi2 are shown to be associated with tumor initiation, progression, and drug resistance [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 25 , 26 , 36 , 37 , 38 , 39 ]. Importantly, downregulation of Msi1 and Msi2 proteins in tumors results in reduction of their tumorigenic growth [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have demonstrated that MSI2 knockdown enhances p21 protein and mRNA levels, the MSI2-mediated downregulation of p21 protein levels is not entirely mediated by decreased mRNA stability. 32, 47, 48 A previous study reported that cell cycle arrest and apoptosis are induced in MSI2 knockdown cells. 39 Consistent with these findings, apoptosis was inhibited in MSI2-knockdown cells and DBC2-overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%